2010 International Conference on Field Programmable Logic and Applications 2010
DOI: 10.1109/fpl.2010.107
|View full text |Cite
|
Sign up to set email alerts
|

Finding System-Level Information and Analyzing Its Correlation to FPGA Placement

Abstract: Abstract-One of the more popular placement algorithms for Field Programmable Gate Arrays (FPGAs) is called Simulated Annealing (SA). This algorithm tries to create a good quality placement from a flattened design that no longer contains any high-level information related to the original design hierarchy. Unfortunately, placement is an NP-hard problem and as the size and complexity of designs implemented on FPGAs increases, SA does not scale well to find good solutions in a timely fashion. As modern FPGAs can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Applying data-mining to algorithmic results, as described above, provides us with a set of gems. Gems are clusters within the initial digital design that we could not find using upfront clustering techniques with theoretical relationships on the design netlists, 23 but by finding gems, which are localized placement knowledge extracted from repeated runs of the placement algorithm, we can do two things. First, we can use these gems as medium-grain blocks mixed with the unclustered blocks (fine-grain blocks) of the original design to examine new algorithms for placing this distribution of blocks.…”
Section: Methodology For Placement Algorithmic Data-miningmentioning
confidence: 99%
“…Applying data-mining to algorithmic results, as described above, provides us with a set of gems. Gems are clusters within the initial digital design that we could not find using upfront clustering techniques with theoretical relationships on the design netlists, 23 but by finding gems, which are localized placement knowledge extracted from repeated runs of the placement algorithm, we can do two things. First, we can use these gems as medium-grain blocks mixed with the unclustered blocks (fine-grain blocks) of the original design to examine new algorithms for placing this distribution of blocks.…”
Section: Methodology For Placement Algorithmic Data-miningmentioning
confidence: 99%
“…Medium-grained structures are small collections of clusters (between 2 and 10) that are known to be strongly related to one another and should be placed in close proximity to each other on the FPGA. Our terminology for these medium-grained structures is super-clusters [33], which relates to our choice of using the term supergenes. Medium-grained placement would be no different than fine-grain placement if we could completely partition the entire design into the same sized super-clusters that could be placed in grid-like manner, but our research has found that there is only a small percentage of fine-grain clusters that can be organized into super-clusters and these super-clusters can vary in size (how many clusters are included in each).…”
Section: Fine Medium and Course Grain Fpgamentioning
confidence: 99%
“…Our preliminary work [33] describes clustering methods that can find these medium-grained structures during the CAD flow. However, our current findings suggest that these methods do not find high quality superclusters.…”
Section: A Finding Medium-grained Super-clustersmentioning
confidence: 99%